Asteraceae with potential for use in native grasslands and forest fragments: a case study at Santa Rita Farm, Lages - SC - Lapa, Michele Mara da Silva; Bortoluzzi, Roseli Lopes da Costa; Mantovani, Adelar (Revista de Ciências Agroveterinárias, 2024)
The objective of this study was to assess the potential for use of species present in grassland and forest areas located in the Fazenda Santa Rita, with about 200 hectares, located in the Coxilha Rica region, Lages - SC. For the floristic survey, the walking collection method was adopted, from March 2021 to December 2022. Fertile specimens collected in the field were cataloged and incorporated into the LUSC Herbarium, at the University of the State of Santa Catarina. 110 Asteraceae species were identified. For the species use verification stage, scientific articles published in digital journals available in the Scielo, CAPES, and Web of Science databases were searched. In addition, printed books and articles published in specialized botanical journals were consulted to select relevant works on the potential use of Asteraceae species. The keywords used in the research were: "economic use of the Asteraceae family", "Asteraceae for ornamental use", "Asteraceae for medicinal use", "Asteraceae for honey and beekeeping use", "Asteraceae for conventional and non-conventional food use". The name "Asteraceae" was also replaced by "Compositae" in each of the uses, to locate the articles, as well as the individual analysis of the species, which were subsequently evaluated for their potential use. Of the species confirmed in the study area, 60 (54.55%) have information on their use, while for the other 50 (45.45%) species, it was not possible to locate their potential use in the literature. This research highlights the need for basic studies on native species, and the importance of deepening knowledge about their functionalities for the maintenance of ecosystems, which could offer a variety of potential applications.